2016
DOI: 10.3139/146.111423
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal casting technique baseline knowledge, applications, and processing parameters: overview

Abstract: The increasing need for materials with light weight, high resistance to corrosion and wear, toughness and strength, machinability, high thermal capacity etc. for various applications is unending. This demand has continued to stretch the exploitation and manipulation of various functionally graded materials (FGMs) and their production methods. This study explores one of the FGM production processes called the centrifugal casting technique (CCT). The centrifugal casting process has several potential advantages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
0
30
0
1
Order By: Relevance
“…Mujiyono et al (2018) manufactured a BNCT collimator from nickel using centrifugal casting. Casting is a manufacturing method to produce a metal material, and centrifugal casting is a casting method that uses centrifugal force from the rotating mould (Iqbal et al 2014;Ebhota et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mujiyono et al (2018) manufactured a BNCT collimator from nickel using centrifugal casting. Casting is a manufacturing method to produce a metal material, and centrifugal casting is a casting method that uses centrifugal force from the rotating mould (Iqbal et al 2014;Ebhota et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal casting process increases cooling rate and consequently, produces small dendritic cells, small inter-dendrite arm spacing and small lakes of Si. Alloys of Al-Si by CCT are morphologically transformed from acicular to ibrous [52]. Micrographs of A390-5%Mg alloy as-cast fabricated by gravity casting and CCT are shown in Figure 16.…”
Section: Centrifugal Casting Techniquementioning
confidence: 99%
“…Some studies have reported that mould rotational speed range of 1200-1500 RPM as the optimum [53] and other relevant processing parameters are pre-heating and pouring temperatures [52]. The efect of CCT on casting can be classiied into three: centrifugal pressure, inherent vibration of the process and luid dynamics.…”
Section: Centrifugal Casting Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The metal matrix and reinforcement density difference cause segregation in which the particles with higher density move to the outer region and lower density particles migrate to the inner surface. The grading defines the functionality and can be controlled and improved by processing variables such as centrifugal rotation speed, molten metal alloying temperature, particle size and volume, mould temperature, and cast geometry [51].…”
Section: Centrifugal Castingmentioning
confidence: 99%